Caveolin-1 is ubiquitinated and targeted to intralumenal vesicles in endolysosomes for degradation - Hayer, Arnold (The Rockefeller University Press, 2010)
Caveolae are long-lived plasma membrane microdomains composed of caveolins, cavins, and a cholesterol-rich membrane. Little is known about how caveolae disassemble and how their coat components are degraded. We studied the degradation of caveolin-1 (CAV1), a major caveolar protein, in CV1 cells. CAV1 was degraded very slowly, but turnover could be accelerated by compromising caveolae assembly. Now, CAV1 became detectable in late endosomes (LE) and lysosomes where it was degraded. Targeting to the degradative pathway required ubiquitination and the endosomal sorting complex required for transport (ESCRT) machinery for inclusion into intralumenal vesicles in endosomes. A dual-tag strategy allowed us to monitor exposure of CAV1 to the acidic lumen of individual, maturing LE in living cells. Importantly, we found that “caveosomes,” previously described by our group as independent organelles distinct from endosomes, actually correspond to late endosomal compartments modified by the accumulation of overexpressed CAV1 awaiting degradation. The findings led us to a revised model for endocytic trafficking of CAV1.